Performance analysis of complex field network coding based on moment generating function - Gang-zi CHEN; Jing YANG (Tongxin xuebao)
The moment generating function was introduced to analysis closed-form expression for the outage probability that the relays employ complex field network coding,and the effect on symbol error probability with various modulation mode was evaluated.Computer simulation results demonstrate that the difference between closed expression and the approximate representation of outage probability greatly relies on the level of signal to noise ratio.